2002
DOI: 10.1203/00006450-200209000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibition Decreases Cell Turnover in the Neonatal Rat Heart

Abstract: The renin angiotensin system plays an important role in growth and development. Exposure of the neonate to an ACE inhibitor increases mortality and results in growth retardation and abnormal development. We have demonstrated that ACE inhibition in the developing kidney increases apoptosis and decreases cell proliferation, which may account for renal growth impairment. To evaluate the role of endogenous angiotensin in cardiac development, the relationship between ACE inhibition, cell proliferation, apoptosis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…The higher levels of Ki-67 immunolabeling (a marker of cell cycle activity) and lower levels of caspase-3 immunolabeling (a marker of apoptosis) in preterm piglet hearts confirms that at 91 days gestation (equivalent to 25–27 weeks human gestation) the heart is growing by hyperplasia as well as hypertrophy, as seen in other species [12], [34], [35]. During the last weeks of pregnancy in the pig, however, there is evidence that this hyperplastic growth declines since the number of Ki-67 positive nuclei were less at term (Figure 4A), while hypertrophy continued as indicated by the increase in myocyte volume (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
“…The higher levels of Ki-67 immunolabeling (a marker of cell cycle activity) and lower levels of caspase-3 immunolabeling (a marker of apoptosis) in preterm piglet hearts confirms that at 91 days gestation (equivalent to 25–27 weeks human gestation) the heart is growing by hyperplasia as well as hypertrophy, as seen in other species [12], [34], [35]. During the last weeks of pregnancy in the pig, however, there is evidence that this hyperplastic growth declines since the number of Ki-67 positive nuclei were less at term (Figure 4A), while hypertrophy continued as indicated by the increase in myocyte volume (Figure 2).…”
Section: Discussionsupporting
confidence: 53%
“…In addition, angiotensin II promotes cell growth via angiotensin II type I (AT1) receptors in cardiac myocytes, which cause inotropic and chronotropic changes and induce apoptosis in myocytes (14). A number of studies have demonstrated that alterations in the RAAS of developing rats affect cardiac growth and development (1, 15). A recent new wave of interest in aldosterone physiology has been generated by its role in cardiovascular homeostasis including blood-pressure homeostasis, myocardial fibrosis and remodeling of blood vessels (6).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that alterations in the renin angiotensin aldosterone system (RAAS), of the developing rat, affect cardiac and renal growth and development (1). To date, many studies have reported that RAAS plays a major role in the pathophysiology of the cardiovascular system (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated that Ang II modulates growth in a variety of tissues, including the kidney and the heart (7, 8, 12, 13). Ang II inhibition by angiotensin converting enzyme (ACE) inhibitor in the developing rat kidney decreases the cellular proliferation and increases apoptosis, and this may account for neonatal renal growth impairment (7, 8, 12-15).…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was performed on paraffin sections as described previously (7, 8). The proliferating cell nuclear antigen (PCNA) cells and terminal deoxynucleotide transferase-mediated nick-end labeling (TUNEL)-positive apoptotic cells were detected using the avidin-biotin immunoperoxidase method (Vectastain ABC kit, Burlingame, CA, U.S.A.) and the TACS TM 2 TdT In Situ Apoptosis Detection Kit (Trevigen, Gaithersburg, MD, U.S.A.), respectively.…”
Section: Methodsmentioning
confidence: 99%